When chemosociality fails to produce chemosolidarity: public participation and chemical industry parks in China - Lora-Wainwright, A; Lou, LIT (Palgrave Macmillan, 2025)
This article examines the potentials and limitations of the concept of “chemosociality” (Shapiro and Kirksey 2017) through a case study of Emerald, an environmental NGO addressing pollution in China’s chemical industry. Based on fieldwork and online research conducted since 2016, the article explores how chemosociality provides a lens to move beyond binary views of a homogeneous frontline communities battling against toxic industries. However, it argues that chemosociality alone is insufficient to account for the unevenness of community engagement in environmental advocacy. Drawing on Bradley’s concept of biosolidarity (2021), the article introduces chemosolidarity and ecosolidarity to highlight Emerald’s efforts to foster public participation. While Emerald’s attempts to cultivate chemosolidarity were unsuccessful, they nurtured ecosolidarity, grounded in a shared appreciation of nature. This example underscores the need to differentiate between sociality and solidarity and to pay attention to affective rather than effective participation to gain a more nuanced understanding of environmental justice, environmental advocacy and the intricate entanglements it navigates.